KAJIAN USAHATANI KELOMPOK WANITA TANI NAGARI KOTO TUO KECAMATAN HARAU, KAB. 50 KOTA - Rinda Yanti; Hasan Ibrahim; . Muflihayati; Setya Dharma (Partner, 2020)
This research was conducted to answer the questions: 1) How is the KWT farming performance in Nagari Koto Tuo, and 2) Analyzing the factors that influence the farming performance in Nagari Koto Tuo in an effort to support family welfare. The study was conducted by taking a purposive sample on a group of women farmers (99 people) Tanjung Saiyo, Mawar Saiyo, Perpito, Want to Forward, Jaso Tani, Harapan Baru Jorong Padang Rontang Nagari Koto Tuo, Harau District, Tanjung Pati, Limapuluh Kota Regency. The method used is a survey method. Then the data will be analyzed with the SPSS program. Model building factors consist of X1 (food sector), X2 (horticulture sector), X3 (plantations), X4 (livestock), X5 (non-farm activity sector). The results showed that the resulting regression models were: Y = 339821.90 - 1.030X1 + 3,887X2 + 6.019X3 + 0.207X4 + 1,879X5. Farms undertaken by 6 KWT at the research location consist of the food, horticulture, plantation, animal husbandry and non-farming sectors. The contribution of the food sector is negative to KWT revenues due to the high costs incurred by KWT. This case occurred at KWT Harapan Baru. The findings show that the plantation and livestock sector provides a relatively dominant contribution to income when compared to other farming sectors and non-farming sectors. Keywords: Farming, Women Farmers, Models, Food